Air pollutants in Osaka (Japan) - Nakata, Makiko; Sano, Itaru; Mukai, Sonoyo (Frontiers in Environmental Science, 2015)
Increasing emission of anthropogenic particles is causing heavy air pollution. This work intends to analyze the air pollution in greater metropolitan area of Asia and its influence on the environment. We focus on Osaka in Japan because our group has been monitoring suspended particulate matter (PM) at Osaka/AERONET since 2004. PM is usually used as an indicator of air quality, because high PM concentrations can degrade air quality. Osaka is the second largest metropolitan region of Japan and its air is significantly polluted by anthropogenic particles emitted from vehicles and industry. In this study, seasonal variation of air pollutants in Osaka is investigated using ground observations such as PM sampling, AERONET photometry, and numerical model simulation. Results indicate that PM concentrations are high during spring and summer because of yellow dust events and photochemical reactions, respectively. In addition, the impact of anthropogenic PM around Osaka is significant in summer.